Studi Komparasi Performa NGINX dan HAPROXY Sebagai Load Balancer di Cloud Menggunakan Teknologi Kontainer - Joshua Gibeon Mulyana; Willy Sudiarto Raharjo; Gani Indriyanta (Jurnal Terapan Teknologi Informasi, 2021)
High availability and scalability is a must have feature for server that owned by industrial sector. One concept that used by technology practitioner ishorizontal scaling. Horizontal scaling can be achieved by using load balancer. Even though those technology practitioner started to adopt containerization technology, those technology practitioner still using load balancer. The purpose of this research is to compare NGINX and HAPROXY performance as load balancer based on response time and error rate. Both NGINX and HAPROXY will run on docker that installed on various virtual machine type in both AWS and GCP. The result shows that based on writer’s configuration, NGINX could handle medium and heavy load better than HAPROXY. Another result shows that AWS could handle medium and heavy load better than GCP.